2009
DOI: 10.1088/0953-8984/21/32/326002
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing spin state phase separation by strontium addition in the Y (Ba1−xSrx)Co2O5.5layered cobaltite

Abstract: In this paper we present a neutron diffraction study of the effects of replacing Ba with smaller Sr cations in the layered cobaltite YBaCo(2)O(5+δ) for δ≈0.5. Neutron thermodiffractograms are reported in the temperature range 20 K≤T≤300 K, as well as high-resolution neutron diffraction experiments at selected temperatures. The systematic refinement of the series of samples with Sr substituting at the Ba site permits the understanding of the complex magnetic behaviour of this system, and reinforces a two-phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 22 publications
4
19
0
Order By: Relevance
“…It is worth emphasizing that phase segregation into electronrich (ferromagnetic) and electron-poor (antiferromagnetic) phases was earlier claimed for layered cobaltites LnBaCo 2 O 6Àd (Ln-lanthanide). 35 The NPD data permit to clarify the magnetic structure of the La 0.5 Ba 0.5 CoO 2.88 . Taking into account the SPD data for La 0.5 Ba 0.5 CoO 2.88 , the additional peaks occurring only on NPD patterns below 150 K can be referred to magnetic neutron scattering (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It is worth emphasizing that phase segregation into electronrich (ferromagnetic) and electron-poor (antiferromagnetic) phases was earlier claimed for layered cobaltites LnBaCo 2 O 6Àd (Ln-lanthanide). 35 The NPD data permit to clarify the magnetic structure of the La 0.5 Ba 0.5 CoO 2.88 . Taking into account the SPD data for La 0.5 Ba 0.5 CoO 2.88 , the additional peaks occurring only on NPD patterns below 150 K can be referred to magnetic neutron scattering (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The polycrystalline samples used in the present work correspond to those reported in Refs. [13] for x Sr = 0 and [14] for x Sr = 0.05 and x Sr = 0.10. Between the previous and present experiments, samples were stored in a dessicator containing silica gel, at room temperature (RT) and ambient pressure.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The study on samples substituted with Sr at the Basite confi rmed the phase-separation scenario [19,20]. We found that Sr addition destabilizes the ferrimagnetic SSO phase, as well as the "122" order, favoring instead a tetragonal and less ordered structure (Figure 3).…”
Section: Crystallography and Magnetism In Cobalt Oxidesmentioning
confidence: 53%
“…Moreover, the member with R = Ca was recently found to be multiferroic [22]. Data were collected at ILL (D20) with λ ∼ 2.42 Å in the temperature range 20-310 K (adapted from [19]). It is only through NPD experiments that the identity of these arrangements could be revealed (Figure 4), giving us a clue on the relevant magnetic interactions in the system, and unveiling how their stability may be tuned using variables such as composition, magnetic fi eld and temperature.…”
Section: Crystallography and Magnetism In Cobalt Oxidesmentioning
confidence: 99%